Pengaruh Indeks Harga Global Terhadap Pergerakan Indeks Harga Gabungan - Dede Suharna (The Asia Pacific Journal Of Management Studies, 2014)
Globalization is one of the important issues that have changed investment environment. The development of a country's economy cannot be separated from the country's stock index movement, because the movement of stock indices followed the optimism and pessimism of stock investors. The purpose of this study was to examine the influence of the NYSE index, NIKKEI, FTSE and SSE to JCI. This study uses a correlational approach with data analysis techniques with multiple regression analysis and assisted by using SPSS for Windows version 20. The population in this study is a report on global stock indices, so that the sample used is Composite Stock Price Index (CSPI) in the period January 2011 to by March 2014 when the closing price from January 2001 to March 2014 so that there are 160 data. Results of statistical calculations found that (1) There is a positive influence on the NYSE Composite Index; (2) There is a positive influence NIKKEI against JCI; (3) There is a positive influence on the FTSE JCI; and (4) There is no positive impact on JCI SSE.